Relocation of 3 April 2017 Moiyabana Earthquake in Botswana Using Seismological Data from Local Network of Autonomously Recording Seismographs and International Monitoring System Stations - Simon, Rapelang E.; King, J. G.; Moffat, L. C.; Moidaki, M. D.; Kwadiba, M. T. O.; Jackson, K. G.; Ntibinyane, O.; Ranganai, R. T. (Pure and applied geophysics, 2024)
On the 3rd April 2017 a widely felt Moiyabana earthquake shook Botswana and the rest of southern Africa. Previous Moiyabana earthquake locations used mainly teleseismic or regional seismograms; and/or non-seismic methods which include Synthetic Aperture Radar (InSAR), and magnetotelluric (MT). These results did not agree, as evidenced by the depth of the earthquake that ranged from zero to 30 km (i.e. indicating either a man-made event or a natural event); thus motivating us to re-assess the location parameters. Unfiltered seismic waveform data from the recent project of the Network of Autonomously Recording Seismographs (NARS) in Botswana was complimented with stations from the International Monitoring System (IMS) to relocate the event. Relocated parameters are origin time, epicentre, focal depth, and magnitude. Geotool software from the Comprehensive Nuclear Test Ban Treaty Organization (CTBTO), and the Regional Seismic Travel Time model (RSTT) were used to process vertical components waveforms from 9 NARS and 32 IMS stations. Geotool results are: earthquake epicentre (22.645 °S: 25.220 °E); origin time of 17:40:16.9 (UTC); hypocentral depth range of 22 to 24 km; body magnitude (mb) and local magnitude (ml) of 6.3 ± 0.6 and 6.0 ± 0.8, respectively. RSTT results are: earthquake epicentre (22.667 °S: 25.257 °E); origin time of 17:40:16.95 (UTC); hypocentral depth of 25 km; and mb of 6.65 ± 0.03. The seismological location parameters from Geotool and RSTT, agree very well within experimental uncertainties with the non-seismic geophysical methods.